Negative plate and battery
By using a first conductive adhesive with a three-dimensional structure in the basecoat layer of the negative electrode sheet, the problem of poor bonding force of the negative electrode sheet of the lithium-ion battery is solved, and the energy density, circulation performance and fast charging performance of the battery are improved.
Patent Information
- Application Number
- CN202411924900.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
The negative electrode sheet of the lithium-ion battery has weak bonding force and the current collector, resulting in poor bonding force, easy material drop, and the battery performance declines due to expansion and contraction during the cycle.
A first conductive adhesive having a three-dimensional structure, including a first carbon nanotube, is added to the basecoat of the negative electrode sheet, to enhance the ability of the embedded or disengagement of lithium ions and to improve the electron and ion conduction capabilities by forming a three-dimensional conductive network.
By reducing the thickness of the basecoat layer, the thickness of the negative electrode sheet is optimized and the energy density of the battery is improved; the adhesion between the negative electrode current collector and the active material layer is enhanced, the processing and circulation performance of the electrode sheet is improved; and the fast charging performance of the battery is improved.
Smart Images

Figure CN119673950A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a battery comprising the negative electrode sheet. Background Art
[0002] At present, the negative electrode sheets of lithium-ion batteries have weak interfacial bonding strength between the negative electrode active material and the current collector during coating, resulting in poor adhesion of the negative electrode active material, which is prone to problems such as electrode sheet falling off in the later process. In addition, the expansion and contraction of the negative electrode active material during the cycle causes it to separate from the current collector, affecting battery performance.
[0003] The conventional solution to the above problems is to introduce a carbon coating layer on the current collector: the use of a combination of conductive carbon black and a binder can initially improve the above problems, but the increase in the thickness of the carbon coating layer will affect the energy density of the battery, and the use of a large amount of binder in the carbon coating layer will also lead to an increase in the electrode resistivity, affecting the fast charging performance of the battery. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art, and provide a negative electrode sheet and a battery including the negative electrode sheet. The negative electrode sheet of the present invention can significantly reduce the thickness of the base coating, thereby optimizing the thickness of the negative electrode sheet and increasing the energy density of the battery; it can enhance the bonding force between the negative electrode current collector and the negative electrode active material layer, improve the structural stability of the active material layer, improve the deformation and powder loss of the electrode sheet during electrode sheet processing and battery cycle, and inhibit cycle expansion; improve the conductivity of the electrode sheet and improve the fast charging performance of the battery.
[0005] A first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector, a primer layer and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, wherein the primer layer is located between the negative electrode current collector and the negative electrode active material layer, the primer layer comprises a three-dimensional structure formed by a first conductive adhesive, the first conductive adhesive comprises a first carbon nanotube, and the negative electrode sheet satisfies the following relationship: 1.2≤B / K≤3.4, wherein B is the aspect ratio of the first carbon nanotube, and K is the tensile strength of the negative electrode current collector, in MPa.
[0006] A second aspect of the present invention provides a battery, comprising the negative electrode sheet described in the first aspect of the present invention.
[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0008] (1) The negative electrode sheet of the present invention can significantly reduce the thickness of the base coating layer by adding a first conductive binder having a three-dimensional structure to the base coating layer, thereby optimizing the thickness of the negative electrode sheet and improving the battery energy density;
[0009] (2) The bottom coating layer of the negative electrode sheet of the present invention can increase the bonding force between the negative electrode current collector and the negative electrode active material layer, improve the structural stability of the negative electrode active material layer, improve the deformation and powder loss of the electrode sheet during electrode sheet processing and battery cycle, and inhibit cycle expansion;
[0010] (3) The bottom coating of the negative electrode sheet of the present invention has higher electronic conductivity and ionic conductivity; the ability of lithium ion embedding or extraction is stronger, and the electron transmission rate is faster, thereby improving the fast charging performance of the battery.
[0011] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Shown are the structural schematic diagrams of the negative electrode sheet and the structural schematic diagram of the bottom coating layer of the present invention.
[0014] Figure 2 Shown is a cross-sectional SEM image of the bottom coating of the negative electrode sheet in one example of the present invention.
[0015] Description of reference numerals:
[0016] The negative electrode current collector 100 , the undercoat layer 200 , the negative electrode active material layer 300 , the first conductive binder 210 , the first carbon black 220 , the second conductive binder 310 , the negative electrode active material 320 , the second carbon black 330 , and the second dispersant 340 . DETAILED DESCRIPTION
[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.
[0018] A first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector, a primer layer and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, wherein the primer layer is located between the negative electrode current collector and the negative electrode active material layer, the primer layer comprises a three-dimensional structure formed by a first conductive adhesive, the first conductive adhesive comprises a first carbon nanotube, and the negative electrode sheet satisfies the following relationship: 1.2≤B / K≤3.4, wherein B is the aspect ratio of the first carbon nanotube, and K is the tensile strength of the negative electrode current collector, in MPa.
[0019] like Figure 1 As shown, the negative electrode sheet includes a negative electrode collector 100, a primer layer 200 and a negative electrode active material layer 300 located on one side or both sides of the negative electrode collector 100, the primer layer 200 is located between the negative electrode collector 100 and the negative electrode active material layer 300, and the primer layer 200 includes a three-dimensional structure formed by a first conductive adhesive 210, and the first conductive adhesive 210 includes a first carbon nanotube.
[0020] In the present invention, by adding a first conductive binder with a three-dimensional structure to the bottom coating, the first conductive binder includes a first carbon nanotube, wherein both ends of the first carbon nanotube in the three-dimensional network skeleton can be uniformly embedded in the positive electrode sheet, forming a three-dimensional conductive network in the bottom coating, which can make the ability of lithium ion embedding or extraction stronger, and have higher electronic conductivity and ion conductivity, thereby improving the electronic and ion conductivity of the negative electrode sheet, reducing the transmission resistance of electrons, reducing battery polarization, and improving the cycle performance and fast charging performance of the battery; and the first carbon nanotubes in the first conductive binder with a three-dimensional structure are in full and close contact with each other, greatly improving the compaction density of the bottom coating, reducing the thickness of the bottom coating, thereby reducing the overall thickness of the electrode sheet, and increasing the energy density of the battery. At the same time, the first conductive binder with a three-dimensional network skeleton can improve the adhesion of the bottom coating, thereby enhancing the interface bonding force between the bottom coating and the negative electrode collector, so that the bonding force between the negative electrode active material layer arranged on the bottom coating and the negative electrode collector is stronger, and the structural stability of the negative electrode active material layer is improved, thereby improving the deformation of the electrode sheet and the powder falling of the electrode sheet during the electrode sheet processing and battery cycle.
[0021] Further, in the present invention, the negative electrode sheet can satisfy the following relationship: 1.2≤B / K≤3.4, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3 or 3.4, wherein B is the aspect ratio of the first carbon nanotubes, and K is the tensile strength of the negative electrode current collector, in MPa. When the above relationship is met, the fracture of the negative electrode sheet caused by cyclic stress can be improved, the toughness of the negative electrode sheet can be improved, the adhesion between the negative electrode active material layer and the negative electrode current collector can be improved, and the expansion of the negative electrode active material can be avoided, resulting in its separation from the current collector, thereby improving the structural strength of the negative electrode sheet as a whole, reducing the extension and deformation of the electrode sheet during rolling, improving the electrode sheet deformation and electrode sheet powder loss problems during electrode sheet processing and battery cycling, and inhibiting cyclic expansion; and, by satisfying the above relationship, the interface impedance between the negative electrode active material layer and the negative electrode current collector can be reduced, and the electrode sheet structural stability and battery performance during the cycle process can be improved; when the ratio of the two is too large, the aspect ratio of the first carbon nanotube is relatively large, and the primer is The hardness of the layer will be too large, and the tensile strength of the negative electrode collector is too low. Then, when the negative electrode sheet is subjected to cyclic stress, the bottom coating will easily crack, causing the bottom coating to separate from the negative electrode collector and the negative electrode active material layer, resulting in an increase in the interface impedance of the electrode sheet; when the ratio of the two is too small, the length-to-diameter ratio of the first carbon nanotube is relatively small, and the mechanical strength of the bottom coating will be too small. At the same time, the tensile strength of the negative electrode collector is relatively strong, but the toughness of the negative electrode collector will be reduced, resulting in the overall strength of the electrode sheet being too poor, and it is more likely to break when subjected to cyclic stress, and the conductivity of the low aspect ratio carbon nanotubes will be lower, and the electronic conductivity and ionic conductivity of the negative electrode sheet will also deteriorate, affecting the fast charging performance of the battery.
[0022] In one example, 2≤B / K≤3.
[0023] By adding a first conductive binder with a three-dimensional structure to the base coating, the energy density of the battery can be improved compared with the prior art, while improving the battery's charging performance, the electrode processing performance, and the structural stability of the electrode during cycling. In order to further improve the effect, one or more of the technical features can be further optimized.
[0024] In the present invention, the first conductive adhesive comprises a first adhesive layer located on at least a portion of the surface of the first carbon nanotube.
[0025] It can be understood that the first bonding layer can be located on the entire surface of the first carbon nanotube, or on a portion of the surface of the first carbon nanotube. Figure 1As shown in the schematic diagram, the black three-dimensional linear structure is the first carbon nanotube, and the red structure on its surface is the first bonding layer, which is located on a portion of the surface of the first carbon nanotube. Wherein, whether the first bonding layer is located on a portion of the surface of the first carbon nanotube or on the entire surface of the first carbon nanotube, the first bonding layer has little or no effect on the conductivity of the first carbon nanotube, so the first carbon nanotube still has conductivity and can meet the conductivity requirements of the negative electrode sheet.
[0026] The first bonding layer located on at least part of the surface of the first carbon nanotubes can make the first carbon nanotubes contact more fully and closely, thereby further improving the compaction density of the base coating, reducing the thickness of the base coating, and thus increasing the energy density of the battery; at the same time, the first bonding layer located on at least part of the surface of the first carbon nanotubes can also improve the adhesion of the base coating, enhance the interfacial bonding force between the base coating and the negative electrode collector, make the bonding force between the negative electrode active material layer arranged on the base coating and the negative electrode collector stronger, improve the structural stability of the negative electrode active material layer, thereby improving the problems of pole piece deformation and pole piece powder falling during pole piece processing and battery cycle.
[0027] In the present invention, the tensile strength K of the negative electrode current collector may be 300Mpa-1000Mpa, for example, 300Mpa, 400Mpa, 500Mpa, 600Mpa, 700Mpa, 800Mpa, 900Mpa or 1000Mpa. When the tensile strength K of the negative electrode current collector is within the aforementioned range, the pole piece can have higher stability during rolling extension and cyclic deformation, and improve the deformation of the pole piece during pole piece processing and cycling. The tensile strength K of the negative electrode current collector is proportional to the thickness of the negative electrode current collector, that is, under the same conditions, the greater the thickness, the higher the tensile strength K; the tensile strength K can be directly measured by using a small tensile machine to perform a tensile test on the negative electrode current collector.
[0028] In one example, the tensile strength K of the negative electrode current collector is 700 MPa-900 MPa.
[0029] In the present invention, the aspect ratio B of the first carbon nanotube can be ≥1000, for example, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 4000 or 5000. When the aspect ratio of the first carbon nanotube is ≥1000, the carbon nanotube with a high aspect ratio will have good flexibility and bendability, thereby improving the flexibility of the pole piece, further improving the processing performance of the pole piece and the structural stability of the pole piece during the cycle, and improving the safety and cycle performance of the battery; at the same time, the carbon nanotube with a high aspect ratio has higher conductivity, and its high specific surface area provides more active contact points, which is more conducive to the electronic conduction of the three-dimensional structure. The aspect ratio B of the first carbon nanotubes=average tube length of the first carbon nanotubes / average tube diameter of the first carbon nanotubes.
[0030] In one example, the aspect ratio B of the first carbon nanotubes is 1800-2100.
[0031] In the present invention, the average diameter and average length of carbon nanotubes refer to the average diameter and length of all carbon nanotubes used in a system. The aspect ratio B of the first carbon nanotube can be selected during the preparation of the primer slurry to meet the requirements of the aspect ratio of carbon nanotubes in the primer. The aspect ratio B of the first carbon nanotube can also be measured by scanning electron microscopy after the positive electrode sheet is prepared. Within a range of 20μm×20μm, the tube diameters and tube lengths of all carbon nanotube bundles in the range are counted, the width of the outer diameter of the carbon nanotube bundle is measured once at three different positions of each bundle, and recorded as the tube diameter of the carbon nanotube bundle. The average tube diameter of all carbon nanotube bundles in the area is taken as the average tube diameter, and the average tube length of all carbon nanotube bundles in the area is taken as the average tube length. Then, the aspect ratio of the carbon nanotube can be obtained through the aspect ratio calculation formula (aspect ratio B of the first carbon nanotube=average tube length of the first carbon nanotube / average tube diameter of the first carbon nanotube). At this time, the size parameters of the carbon nanotubes obtained are almost consistent with the size parameters when the carbon nanotubes are selected.
[0032] In the present invention, the primer layer 200 may further include a first carbon black 220, such as Figure 1 As shown, the first carbon black 220 is located in the gap of the three-dimensional structure. The carbon black located in the gap of the three-dimensional structure in the base coating layer can be used to improve the conductivity of the base coating layer, because the carbon black and the conductive adhesive of the present invention will form a three-dimensional network structure to make up for the pores in the interweaving process of the pure carbon nanotubes. The two work together to form a complete conductive network on the foil base coating, so that the transition interface contact between the negative electrode current collector and the negative electrode active material layer is more sufficient.
[0033] In the present invention, the first carbon nanotube may include a first multi-walled carbon nanotube and / or a first single-walled carbon nanotube. Single-walled carbon nanotubes have a larger tube length, a smaller tube diameter, and a larger specific surface area. For the same number of single-walled carbon nanotubes and multi-walled carbon nanotubes, the former has a larger contact area with the positive electrode active material, and the contact is more sufficient, which has a more obvious improvement in the bonding force in the positive electrode active material layer; in addition, the conductive network of the single-walled carbon nanotube extends longer and wider, and the improvement in the conductivity of the bottom coating is also more obvious, further reducing the internal impedance of the battery and improving its rate discharge. Multi-walled carbon nanotubes have higher strength and rigidity. At the same time, the inclusion of multi-walled carbon nanotubes can improve the structural strength of the three-dimensional network skeleton of the conductive binder, improve the structural stability of the bottom coating, and improve the later cycle performance of the battery.
[0034] In the present invention, the surface of the first carbon nanotube includes one or more of the following functional groups: carboxyl, hydroxyl, amine, and silane. The above functional groups are polar groups, the H atoms of which are easily reduced and easily react with Li in the lithium ion battery electrolyte. + A replacement reaction occurs to complex the conduction of lithium ions and increase the conduction rate of lithium ions, thereby increasing the ion conductivity of the first carbon nanotube, thereby reducing the electrode polarization of the lithium ion battery and lowering the battery impedance.
[0035] In the present invention, the first carbon nanotube is a carbon nanotube modified by the first modifier, and the first modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate, methacrylic acid, and maleic acid.
[0036] In the present invention, the primer layer also includes a first dispersant. The dispersant in the primer layer can act on the primer slurry homogenization process. The first conductive binder with a high aspect ratio has a large specific surface area and is difficult to be dispersed in solvent water. The introduction of the dispersant can quickly disperse the first conductive binder and carbon black in the primer layer, and provide a suspension stabilization effect to prevent the primer slurry from settling and agglomerating, and at the same time provide viscosity characteristics that are conducive to the coating of the primer layer, so that it can be leveled and evenly distributed on the negative electrode current collector.
[0037] In the present invention, the weight ratio of the first multi-walled carbon nanotubes to the first single-walled carbon nanotubes is (2-5):1, for example, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5:1. When the weight ratio of the first multi-walled carbon nanotube to the first single-walled carbon nanotube is less than 2:1, the weight of the first multi-walled carbon nanotube is less and the weight of the first single-walled carbon nanotube is more, which will reduce the mechanical strength of the three-dimensional structure. The single-walled carbon nanotube is composed of a single layer of graphene and has poor tensile strength. A sufficient amount of multi-layered multi-walled carbon nanotubes is required to improve the overall mechanical strength; when the weight ratio of the first multi-walled carbon nanotube to the first single-walled carbon nanotube is greater than 5:1, the weight of the first multi-walled carbon nanotube is more and the weight of the first single-walled carbon nanotube is less, which will greatly reduce its conductivity. The single-walled carbon nanotube has a high aspect ratio and a high specific surface area and has excellent conductivity. The use design requires sufficient single-walled carbon nanotubes to meet the electronic conductivity.
[0038] In one example, the ratio of the weight of the first multi-walled carbon nanotubes to the weight of the first single-walled carbon nanotubes is (3-4):1.
[0039] In the present invention, the weight ratio of the first carbon nanotubes to the first carbon black is (1.22-5.84):1, for example, 1.22:1, 1.3:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 3:1, 3.2:1, 3.5:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.8:1, 5:1, 5.2:1, 5.4:1, 5.6:1, 5.8:1, 5.82:1 or 5.84:1. An appropriate amount of carbon black located in the gaps of the three-dimensional structure in the base coating layer can be used to improve the conductivity of the base coating layer. However, when the weight proportion of the first carbon black in the base coating layer is too large, it will cause excessive accumulation of carbon black distribution, which will reduce the conductivity efficiency of the base coating layer per unit mass. At the same time, the carbon black particle size is larger than the first conductive binder particle, which will increase the thickness of the base coating layer. Therefore, the weight proportion of the first carbon nanotube to the weight of the first carbon black can be controlled so that its weight proportion will not be too large; at the same time, the weight proportion of the first carbon black in the base coating layer relative to the first carbon nanotube should not be too small, because a small amount of carbon black cannot make up for the tube bundle network pores formed by the first conductive binder, reducing the direct contact area between the first conductive binder and the negative electrode current collector. At the same time, the appropriate amount of carbon black can also enhance the mechanical toughness of the electrode.
[0040] In one example, the ratio of the weight of the first carbon nanotubes to the weight of the first carbon black is (2.5-3.5):1.
[0041] In the present invention, the ratio of the thickness of the negative electrode current collector to the thickness of the primer layer is (6-10):1, for example, 6:1, 7:1, 8:1, 9:1 or 10:1. The thickness of the primer layer is relatively low relative to the thickness of the negative electrode current collector, which can optimize the thickness of the negative electrode sheet and improve the energy density of the battery. Furthermore, by setting the thickness of the negative electrode current collector to 6-10 times the thickness of the primer layer, the mechanical strength and conductivity of the primer foil can be taken into account. When the ratio of the thickness of the negative electrode current collector to the primer layer is too small, the overall strength of the negative electrode current collector will be reduced, and the ductility will be insufficient, and it is easy to break during the deformation of the battery electrode sheet; when the ratio is too large, the primer layer is too thick, and the interface conductivity between the negative electrode current collector and the negative electrode active material layer will be correspondingly reduced, which seriously affects the fast charging and cycle performance of the battery.
[0042] In one example, the ratio of the thickness of the negative electrode current collector to the thickness of the primer layer is (8-9):1.
[0043] In the present invention, the thickness of the negative electrode current collector is 3 μm-15 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.
[0044] In the present invention, the thickness of the primer layer is 0.3 μm-0.6 μm, for example, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm or 0.6 μm.
[0045] In the present invention, the average particle size of the carbon black is 10nm-300nm, for example, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 140nm, 160nm, 180nm, 200nm, 210nm, 230nm, 250nm, 270nm, 290nm or 300nm.
[0046] In one example, the average particle size of the first carbon black is 500 nm-3000 nm.
[0047] In the present invention, the first bonding layer further comprises one or more polymers selected from styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), polyacrylic acid (PAA) and polyimide (PI).
[0048] In the present invention, the glass transition temperature of the first adhesive layer is -10°C to 80°C, for example, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C. The glass transition temperature of the first adhesive layer is related to the specific polymer component contained in the first adhesive layer.
[0049] In one example, the glass transition temperature of the first bonding layer is 40°C to 80°C.
[0050] In the present invention, the average thickness of the first bonding layer on the first carbon nanotube is 20nm-200nm, for example, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm or 200nm. The average thickness of the first bonding layer on the first carbon nanotube can be measured by a scanning electron microscope. Within the range of 20μm×20μm, the diameters of all conductive adhesives within the range are counted, and the average value is taken as the average diameter H1 of the conductive adhesive. At the same time, the average diameter of the first carbon nanotube in the conductive adhesive before modification is tested as H2, and finally the average thickness of the first bonding layer on the first carbon nanotube is obtained as H1-H2. The average thickness of the first bonding layer on the first carbon nanotubes can directly affect the bonding strength and conductive properties of the conductive adhesive. When the average thickness of the first bonding layer on the first carbon nanotubes is less than 20nm, the bonding performance of the conductive adhesive will be insufficient, and the coating will not be able to meet the interface bonding requirements of the negative active material layer of the lithium battery pole piece and the negative current collector. The thicker the first bonding layer, the more polymer molecular chains per unit area, and the stronger the binding ability for the negative current collector and the negative active material layer. However, high molecular polymers are non-conductive materials, and their electronic conductivity will be greatly reduced. Therefore, when the average thickness of the first bonding layer on the first carbon nanotubes is greater than 200nm, the electronic conductivity of the conductive adhesive will be reduced, affecting the fast charging and cycle performance of the battery.
[0051] In one example, an average thickness of the first bonding layer on the first carbon nanotubes is 40 nm-100 nm.
[0052] In the present invention, the molecular weight of the polymer in the first bonding layer is ≥ 1 million g / mol, for example, 1 million g / mol, 1.1 million g / mol, 1.2 million g / mol, 1.3 million g / mol, 1.4 million g / mol, 1.5 million g / mol, 1.6 million g / mol, 1.7 million g / mol, 1.8 million g / mol, 1.9 million g / mol or 2 million g / mol. The larger the molecular weight of the polymer in the first bonding layer, the longer its molecular chain is, providing more cross-linking points. At the same time, the higher the molecular weight, the stronger the interaction between molecules, forming a more compact molecular structure, and the higher the bonding strength. When the molecular weight of the polymer in the first bonding layer is greater than 1 million g / mol, the adhesion requirement of the conductive adhesive primer layer can be met.
[0053] In one example, the molecular weight of the polymer in the first bonding layer is 1 million g / mol-1.5 million g / mol.
[0054] In the present invention, the weight ratio of the first carbon nanotubes to the first bonding layer in the first conductive adhesive is (34%-68%):(66%-32%), for example, 34%:66%, 40%:60%, 45%:55%, 50%:50%, 55%:45%, 60%:40%, 65%:35% or 68%:32%. It is understood that the weight content of the first carbon nanotubes can be in the range of 34%-68%, and the weight content of the first bonding layer can be in the range of 66%-32%, but it needs to be satisfied that the sum of the weight content of the first carbon nanotubes and the weight content of the first bonding layer is 100%.
[0055] In the present invention, the first dispersant includes one or more of polyvinyl pyrrolidone (PVP), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA).
[0056] In the present invention, the molecular weight of the first dispersant is 10000 g / mol-100000 g / mol, for example, 10000 g / mol, 20000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, 90000 g / mol or 100000 g / mol.
[0057] In one example, the molecular weight of the first dispersant is 20000 g / mol-40000 g / mol.
[0058] In the present invention, based on the total weight of the primer layer, the weight content of the first conductive adhesive is 72%-86%, for example, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85% or 86%, the weight content of the first carbon black is 10%-20%, for example, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, and the weight content of the first dispersant is 4%-8%, for example, 4%, 5%, 6%, 7% or 8%.
[0059] In the present invention, the average diameter of the first carbon nanotubes is 6 nm-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0060] In one example, the average diameter of the first carbon nanotubes is 6 nm-8 nm.
[0061] In the present invention, the average tube length of the first carbon nanotubes is 13 μm-20 μm, for example, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.
[0062] In one example, the average tube length of the first carbon nanotubes is 13 μm-15 μm.
[0063] In the present invention, the wall thickness of the first carbon nanotube is 6nm-9nm, for example, 6nm, 6.1nm, 6.2nm, 6.3nm, 6.4nm, 6.5nm, 6.6nm, 6.7nm, 6.8nm, 6.9nm or 7nm, 8nm, 9nm.
[0064] In one example, the wall thickness of the first carbon nanotube is 6 nm-6.8 nm.
[0065] In the present invention, the weight proportion of the first carbon nanotubes with an average tube length of ≥8 μm in the first carbon nanotubes is ≥50%, for example, 50%, 60%, 70%, 80%, 90% or 100%. The weight proportion of the first carbon nanotubes with an average tube length of ≥8 μm is ≥50%, which can further improve the electronic conductivity and ionic conductivity of the bottom coating, enhance the ability of lithium ion embedding or de-embedding, and increase the electron transmission rate, thereby further improving the fast charging performance of the battery.
[0066] In one example, the weight of the first carbon nanotubes with an average tube length of ≥8 μm accounts for 50%-60% of all the first carbon nanotubes.
[0067] In the present invention, the surface density of the primer layer is 0.2 g / m 2 -0.8g / m 2 , for example 0.2 g / cm 2 , 0.3g / cm 2 , 0.4g / cm 2 , 0.5g / cm 2 , 0.6g / cm 2 , 0.7g / cm 2 or 0.8g / cm 2 In the present invention, the surface density refers to the single-sided surface density. For example, the surface density of the primer layer refers to that when there is a primer layer on one side of the negative electrode current collector, the surface density of the primer layer is the surface density of that side (i.e., the side with the primer layer); when there are primer layers on both sides of the negative electrode current collector, the densities of the two sides of the primer layer are the same, and the surface density of the primer layer is the surface density of either side.
[0068] In one example, the surface density of the base coating is 0.4 g / m 2 -0.6g / m 2.
[0069] In the present invention, if Figure 1 As shown, the negative electrode active material layer 300 includes a three-dimensional network skeleton and a negative electrode active material 320 located in the three-dimensional network skeleton, the three-dimensional network skeleton is formed by a second conductive binder 310, and the second conductive binder 310 includes a second carbon nanotube and a second bonding layer located on at least a portion of the surface of the second carbon nanotube. In addition, the negative electrode active material layer 300 may also include a second carbon black 330 and a second dispersant 340.
[0070] In the present invention, the peel strength between the primer layer and the negative electrode current collector is ≥10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m, 18N / m, 19N / m, 20N / m, 21N / m, 22N / m, 23N / m, 24N / m, 25N / m, 26N / m, 27N / m, 28N / m, 29N / m, 30N / m, 31N / m, 32N / m, 33N / m, 34N / m or 35N / m.
[0071] In one example, the peel strength between the primer layer and the negative electrode current collector is 12 N / m-18 N / m.
[0072] In the present invention, the negative electrode sheet satisfies the following relationship: 14.4≤K1 / K2≤43, for example, 14.4, 15, 16, 17, 18, 19, 20, 22, 24, 26, 28, 30, 31, 33, 35, 37, 39, 40, 41, 42 or 43, wherein K1 is the crosslinking coefficient between the first conductive binder and the first carbon black, and K2 is the crosslinking coefficient between the second conductive binder and the negative electrode active material.
[0073] In the present invention, the crosslinking coefficient between the first conductive binder and the first carbon black represents the average number of first conductive binders contacted by the surface of a single first carbon black particle. It is understood that the crosslinking coefficient between the first conductive binder and the first carbon black particle is a dimensionless constant, which can be obtained by testing in the following way: within an area of 100 μm*100 μm on the surface of the primer layer, 50 first carbon black particles are randomly selected, and the number of first conductive binders contacted by the surface of each first carbon black particle is calculated, and the crosslinking coefficient between the first conductive binder and the first carbon black = (the sum of the number of first conductive binders contacted by the surfaces of 50 first carbon black particles) / 50.
[0074] In the present invention, the cross-linking coefficient between the second conductive binder and the negative electrode active material represents the average number of the second conductive binder contacted by the surface of a single negative electrode active material particle. It is understood that the cross-linking coefficient between the second conductive binder and the negative electrode active material is a dimensionless constant, which can be obtained by testing in the following way: within an area of 100 μm*100 μm on the surface of the negative electrode active material layer, 50 particles of the negative electrode active material are randomly selected, and the number of the second conductive binder contacted by the surface of each negative electrode active material particle is calculated, and the cross-linking coefficient between the second conductive binder and the negative electrode active material = (the sum of the number of the second conductive binder contacted by the surface of 50 negative electrode active material particles) / 50.
[0075] The present invention can improve the adhesion between the negative electrode active material layer and the bottom coating layer by making the negative electrode sheet satisfy the relationship: 14.4≤K1 / K2≤43, and can keep the overall hardness and toughness of the electrode sheet suitable, on the one hand, preventing the active layer from cracking and powdering during the winding process, and on the other hand, can keep the hardness and toughness of the current collector suitable with the expansion stress of the active layer, prevent the cyclic stress from causing cracks between the active layer and the current collector, increase the interface impedance, and can improve the conductivity of the electrode sheet in the thickness direction, improve the transmission of lithium ions in the thickness direction, and prevent lithium precipitation.
[0076] In the present invention, K1 is 3.6-8.6, for example, 3.6, 3.7, 3.8, 3.9, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.1, 5.3, 5.5, 5.7, 5.9, 6, 6.1, 6.3, 6.5, 6.7, 6.9, 7, 7.2, 7.4, 7.6, 7.8, 8, 8.1, 8.3, 8.5 or 8.6.
[0077] In one example, K1 is 4-5.
[0078] In the present invention, K2 is 0.2-2.5, for example, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.1, 2.2, 2.3, 2.4 or 2.5.
[0079] In one example, K2 is 1-2.
[0080] In the present invention, the surface of the second carbon nanotube includes one or more of the following functional groups: carboxyl group, hydroxyl group, amine group, and silane group.
[0081] In the present invention, the second carbon nanotubes are carbon nanotubes modified by the second modifier, and the second modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate, methacrylic acid, and maleic acid.
[0082] In the present invention, the aspect ratio of the second carbon nanotubes is ≥1000, for example, 1500, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, 12000, 13000, 14000, 15000, 16000, 17000, 18000, 19000 or 20000.
[0083] In one example, the aspect ratio of the second carbon nanotubes is 1800-2500.
[0084] In the present invention, the average diameter of the second carbon nanotubes is 6 nm-10 nm, for example, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0085] In one example, the average diameter of the second carbon nanotubes is 8 nm-10 nm.
[0086] In the present invention, the average tube length of the second carbon nanotubes is 13 μm-20 μm, for example, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.
[0087] In one example, the average tube length of the second carbon nanotubes is 18 μm-20 μm.
[0088] In the present invention, the wall thickness of the second carbon nanotube is 6 nm-9 nm, for example, 6 nm, 6.1 nm, 6.2 nm, 6.3 nm, 6.4 nm, 6.5 nm, 6.6 nm, 6.7 nm, 6.8 nm, 6.9 nm or 7 nm.
[0089] In one example, the wall thickness of the second carbon nanotube is 8 nm-8.8 nm.
[0090] In the present invention, the weight proportion of second carbon nanotubes with an average tube length ≥ 8 μm in all second carbon nanotubes is ≥ 50%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%.
[0091] In one example, the weight of the second carbon nanotubes with an average tube length of ≥8 μm accounts for 50%-70% of all the second carbon nanotubes.
[0092] In one example, the second adhesive layer includes one or more polymers selected from the group consisting of styrene-butadiene rubber (SBR), nitrile-butadiene rubber (NBR), polyacrylic acid (PAA), and polyimide (PI).
[0093] In one example, the second dispersant includes one or more of polyvinyl pyrrolidone (PVP), carboxymethyl cellulose (CMC) and polyacrylic acid (PAA).
[0094] In the present invention, the weight ratio of the second carbon nanotubes to the second bonding layer in the second conductive adhesive is (34%-68%):(66%-32%), for example, 34%:66%, 40%:60%, 45%:55%, 50%:50%, 55%:45%, 60%:40%, 65%:35% or 68%:32%. It is understood that the weight content of the second carbon nanotubes can be in the range of 34%-68%, and the weight content of the second bonding layer can be in the range of 66%-32%, but it needs to be satisfied that the sum of the weight content of the second carbon nanotubes and the weight content of the second bonding layer is 100%.
[0095] In the present invention, the surface density of the negative electrode sheet is 26.82 g / m 2 -134.1g / m 2 , refers to the single-sided surface density of the negative electrode sheet. For example, when there is a negative electrode active material layer on one side of the negative electrode current collector, the surface density of the negative electrode sheet is the surface density of this side (i.e., the side with the negative electrode active material layer); when there are negative electrode active material layers on both sides of the negative electrode current collector, the densities of the two sides of the negative electrode sheet are the same, and the surface density of the negative electrode sheet is the surface density of any one of the sides; one or both sides of the negative electrode current collector of the present invention include a primer layer and a negative electrode active material layer, so the surface density of the negative electrode sheet actually represents the sum of the single-sided surface densities of the primer layer and the negative electrode active material layer, for example, 26.82 g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2 , 120g / m 2 , 130g / m2 , 131g / m 2 , 132g / m 2 , 133g / m 2 , 134g / m 2 or 134.1g / m 2 The present invention can take into account the overall mechanical strength, toughness and conductivity of the battery pole piece by regulating the sum of the surface density of the undercoat layer and the surface density of the negative electrode active material layer within a suitable range.
[0096] In one example, the sum of the surface density of the undercoat layer and the surface density of the negative electrode active material layer is 60 g / m 2 -90g / m 2 .
[0097] In the present invention, the negative electrode active material includes a carbon-based negative electrode material, and the carbon-based negative electrode material includes at least one of artificial graphite, natural graphite, and hard carbon.
[0098] In one example, the negative electrode active material further includes a silicon-based negative electrode material, and the silicon-based negative electrode material includes at least one of silicon carbon, elemental silicon, and silicon oxygen.
[0099] In one example, the mass content of the carbon-based negative electrode material in the negative electrode active material is 70%-98%, and the mass content of the silicon-based negative electrode material is 2%-30%.
[0100] In the present invention, the negative electrode active material layer also includes a negative electrode binder and a thickener, the thickener includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylic acid (PAA), and the negative electrode binder includes one or more of styrene-butadiene rubber (SBR), styrene-acrylic emulsion, nitrile rubber, polyimide, and acrylic.
[0101] In one example, the thickener has a molecular weight of 500,000 g / mol-1,000,000 g / mol, for example, 500,000 g / mol, 600,000 g / mol, 700,000 g / mol, 800,000 g / mol, 900,000 g / mol or 1,000,000 g / mol.
[0102] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90%-99%, the weight content of the second conductive binder is 0.25%-5%, for example, 0.25%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, the negative electrode binder includes 1%-2%, for example, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, and the weight content of the thickener is ≤1%, for example, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2% or 0.1%.
[0103] In one example, the surface density of the negative electrode active material layer is 26.62 g / m 2 -126.1g / m 2 , for example, 26.62 g / m 2 , 30g / m 2 , 40g / m 2 , 50g / m 2 , 60g / m 2 , 70g / m 2 , 80g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2 , 120g / m 2 , 126.1g / m 2 .
[0104] A second aspect of the present invention provides a battery, which may include the negative electrode sheet described in the first aspect of the present invention.
[0105] The materials of the battery except the negative electrode sheet can be prepared according to the methods in the art, and can achieve the effects brought by the negative electrode sheet of the present invention.
[0106] In one example, the battery is a lithium-ion battery.
[0107] In one example, the battery further includes a positive electrode sheet and a separator.
[0108] In one example, the electrolyte further includes lithium salt and other additives.
[0109] In one example, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB) and lithium tetrafluoroborate (LiBF4).
[0110] In one example, the other additives include one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), 1,3-acrylonitrile lactone (PST), vinylethylene carbonate (VEC), succinonitrile (SN), adiponitrile (ADN) and 1,3,6-hexanetrinitrile (HTCN).
[0111] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.
[0112] In one example, the positive electrode active material includes one or more of lithium cobalt oxide, nickel-cobalt-manganese ternary, lithium iron phosphate, lithium iron manganese phosphate, lithium titanate, and lithium manganese oxide.
[0113] In one example, the positive electrode conductive agent includes one or more of conductive carbon black (SP), acetylene black, graphene, and single-walled carbon nanotubes (SWCNTs).
[0114] In one example, the positive electrode binder includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylic acid.
[0115] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0116] Example 1
[0117] Preparation of base coating slurry:
[0118] The primer layer comprises 80% of a first conductive adhesive (40% of a first carbon nanotube and 60% of styrene-butadiene rubber, wherein the average tube length of the first carbon nanotube is 14 μm, the average tube diameter of the first carbon nanotube is 7 μm, the aspect ratio of the first carbon nanotube is 2000, the tube wall thickness of the first carbon nanotube is 6.4 nm, the molecular weight of the styrene-butadiene rubber is 1.2 million g / mol, and the glass transition temperature of the first adhesive layer is 55° C.), 12% of carbon black (average particle size is 1750 nm), and 12% of polyethylene. The present invention is prepared by mixing 8% of ethylenediaminetetraacetic acid (molecular weight 30000 g / mol) with pyrrolidone (molecular weight 30000 g / mol), and slurrying is performed using a 100L planetary mixer to obtain a primer slurry with a solid content of 10% and a viscosity of 50 mPa.s. A 320-mesh gravure roller with a roller radius of 80 cm and a gravure coating speed of 20 m / min is used. The baking temperature is 100° C. The primer of the present invention is prepared on the surface of the negative electrode current collector copper foil (tensile strength K=800 Mpa). The surface density of the primer is measured to be 0.5 g / m 2 .
[0119] The first carbon nanotubes include first multi-walled carbon nanotubes and first single-walled carbon nanotubes, the weight ratio of the first multi-walled carbon nanotubes to the first single-walled carbon nanotubes is 3.5:1, and the first single-walled carbon nanotubes and the first multi-walled carbon nanotubes are modified using first modifiers diethyl adipate and methacrylic acid.
[0120] The preparation method of the first conductive adhesive is as follows:
[0121] The styrene-butadiene rubber with a molecular weight of 1.2 million g / mol is fully dispersed in dimethyl phthalate, the rotation is set to 800 rpm, and the mixture is stirred for 30 minutes to obtain a mixed solution; then the first carbon nanotubes are placed in a deposition reactor, vacuumed, and then the mixed solution obtained in the previous step is passed through the deposition reactor, and the deposition temperature is set to 250° C. and the deposition time is 180 minutes. The dimethyl phthalate in the mixed solution will slowly evaporate and bring out the liquid styrene-butadiene rubber, so that it is deposited on the surface of the carbon nanotubes to form a bonding layer; the carbon nanotubes obtained in the second step and modified by deposition are taken out, which are the first conductive adhesive;
[0122] Preparation of negative electrode active material layer slurry and negative electrode sheet:
[0123] A negative electrode active material layer slurry is prepared according to a certain batching process according to 96.8% negative electrode active material (graphite + silicon carbon, graphite accounts for 90%, silicon carbon accounts for 10%), 1.2% second conductive binder (40% second carbon nanotubes + 60% polyacrylic acid, wherein the average tube length of the second carbon nanotubes is 19μm, the weight proportion of the first carbon nanotubes with an average tube length ≥8μm in the first carbon nanotubes is 55%, the average tube diameter of the second carbon nanotubes is 9μm, the aspect ratio of the second carbon nanotubes is 2111, and the tube wall thickness of the second carbon nanotubes is 8.4nm, and the preparation method of the second conductive binder refers to the preparation method of the first conductive binder), 1% polyacrylic acid (the molecular weight of the thickener is 750000g / mol), and 1% styrene-butadiene rubber. The slurry has a viscosity of 5000mPa.s and a solid content of 50%. The negative electrode active material layer slurry was coated on the negative electrode current collector bottom coating in (1) to prepare a negative electrode sheet. After rolling and slitting, the negative electrode sheet required in this embodiment was obtained. The surface density of the negative electrode sheet was measured to be 75.5 g / m 2 ;
[0124] Among them, the cross-sectional SEM image of the bottom coating of the negative electrode sheet in this embodiment is as follows: Figure 2 As shown, the thickness of the primer layer is 0.444 μm, and the thickness of the negative electrode current collector is 5.97 μm.
[0125] Preparation of positive electrode sheet: According to the ratio of 96% lithium cobalt oxide, 2.5% conductive carbon black, and 1.5% sodium carboxymethyl cellulose, a positive electrode slurry is prepared according to a certain batching process, with a slurry viscosity of 5000mPa.s and a solid content of 75%. The above slurry is sieved and coated on the positive electrode collector, dried at 120°C, and rolled and cut to obtain the positive electrode sheet of this embodiment.
[0126] Preparation of the battery: After rolling and die-cutting the positive and negative electrode sheets obtained above, take the thinned area electrode sheets and assemble them into a core by winding. After passing the short-circuit test, they are packaged with aluminum-plastic film, baked in an oven to remove moisture until the moisture standard required for liquid injection is reached, and then conventional electrolyte in the field is injected. After aging for 24 hours, the first charge is completed by a hot pressing process to obtain an activated battery.
[0127] For specific parameters of this embodiment, please refer to Table 1 and Table 2.
[0128] Example 2 Group
[0129] The second embodiment of the present invention is carried out with reference to the first embodiment, the only difference being that the aspect ratio B of the first carbon nanotube is changed. For details, please refer to Table 1 and Table 2.
[0130] Example 3 Group
[0131] The third group of this embodiment was carried out with reference to the first embodiment, the only difference being that the weight ratio of the first multi-walled carbon nanotube to the first single-walled carbon nanotube in the first carbon nanotube was changed, as shown in Table 1 and Table 2 for details.
[0132] Example 4
[0133] This Example 4 is carried out with reference to Example 1, the only difference being that the first carbon nanotubes are not modified using the first modifier, as shown in Tables 1 and 2 for details.
[0134] Example 5 Group
[0135] The fifth group of this embodiment was carried out with reference to the first embodiment, the only difference being that the weight ratio of the first carbon nanotubes to the first bonding layer in the first conductive adhesive was changed, so that the weight ratio of the first carbon nanotubes to the first carbon black was changed. For details, please refer to Tables 1 and 2.
[0136] Example 6 Group
[0137] The sixth embodiment of the present invention was carried out with reference to the first embodiment, the only difference being that the thickness of the undercoat layer and / or the negative electrode active material layer was changed, so that the ratio of the thickness of the negative electrode current collector to the thickness of the undercoat layer was changed. For details, please refer to Tables 1 and 2.
[0138] Example 7 Group
[0139] The present Example 7 group was carried out with reference to Example 1, with the only difference being that the formula dosage in the second conductive binder, that is, the mass percentage of the second carbon nanotubes and polyacrylic acid, was changed so that the crosslinking coefficient K2 between the second conductive binder and the negative electrode active material was changed. For details, please refer to Tables 1 and 2.
[0140] Example 8
[0141] This Example 8 is carried out with reference to Example 1, with the only difference being that carbon black is not added to the ratio of the primer layer. Specifically, the ratio is 90% of the first conductive adhesive and 10% of polyvinyl pyrrolidone. For details, please refer to Tables 1 and 2.
[0142] Example 9 Group
[0143] The 9th group of this embodiment was carried out with reference to the 1st embodiment, the only difference being that the tensile strength K of the negative electrode current collector copper foil was changed, specifically:
[0144] Example 9-1, the tensile strength of the negative electrode current collector copper foil is K=900K / Mpa;
[0145] Example 9-2, the tensile strength of the negative electrode current collector copper foil is K=300K / Mpa;
[0146] Example 9-3, the tensile strength of the negative electrode current collector copper foil is K=200K / Mpa;
[0147] Example 9-4, the tensile strength of the negative electrode current collector copper foil is K=1200K / Mpa;
[0148] Please refer to Table 1 and Table 2 for details.
[0149] Table 1
[0150]
[0151]
[0152] Table 2
[0153]
[0154] Comparative Example 1
[0155] This comparative example 1 is carried out with reference to Example 1, the only difference being that no primer layer is provided, and a carbon coating layer is provided instead, wherein the carbon coating layer contains 50% carbon black and 50% polyacrylic acid, wherein the thickness of the carbon coating layer is the same as that of the primer layer, and the surface density of the carbon coating layer is 0.9 g / m 2 The surface density of the negative electrode sheet is 75.9g / m 2 .
[0156] Comparative Example 2
[0157] This comparative example 2 is carried out with reference to example 1, the only difference being that the first carbon nanotubes and styrene-butadiene rubber of the first conductive binder in the primer layer are simply mixed in the original proportions, and a mixture of the conductive agent and the binder can be obtained by simple mixing.
[0158] Test Case
[0159] (1) Battery energy density test:
[0160] The ratio of the energy E of the battery prepared in the above embodiments and comparative examples at 0.7C full charge and 0.5C discharge to the cell volume V is the energy density. Specifically: the battery is charged to 4.45V at 0.7C at 25°C, the cut-off current is 0.2C, and then discharged to 3V at 0.5C. The energy is recorded as E1, and the volume energy density of the battery is measured =
[0161] E1 / V*100%, unit is Wh / L, and the test results are recorded in Table 3.
[0162] (2) Battery DCIR test:
[0163] The batteries prepared in the above embodiments and comparative examples are tested for DCIR under 0℃-100% SOC conditions. Specifically: The test method of DCIR is as follows: First, the battery is allowed to stand at 25℃±2℃ for 10 minutes, then the battery is discharged to 3V at 0.2C, allowed to stand for 10 minutes, then charged to 4.45V at 0.7C, with a cut-off current of 0.05C, allowed to stand for 10 minutes, then discharged to 3V at 0.1C, and the initial capacity is recorded as C1, allowed to stand for 10 minutes, then charged to 4.45V at 0.7C, with a cut-off current of 0.05C, allowed to stand for 10 minutes, then discharged at 0.1C for 10s (200ms sampling), and then discharged at 1C. The battery was discharged at 0.1C for 10s (200ms sampling), and then rested for 15min, and then the battery was discharged at 1C for 360s (200ms sampling), and then rested for 15min, until the voltage dropped to 3V. In the step of discharging at 0.1C for 10s, the terminal voltage was marked as V0. In the step of discharging at 1C for 360s, the voltage of the initial 5s of discharge was marked as V1. The DC internal resistance of the battery was recorded as DCIR = (V0-V1) / (1C-0.1C). The test results are recorded in Table 3.
[0164] (3) Low temperature discharge capacity retention rate test of battery:
[0165] The batteries prepared in the above embodiments and comparative examples were tested for discharge capacity retention at 0°C. Specifically: first, the battery was left at 25°C±2°C for 10 min, then discharged at 0.2C to 3V, left at 10 min, then fully charged at 0.7C at 25°C, with a cut-off current of 0.025C, a full charge capacity of C1, left at 10 min, then discharged at 0.2C to 3V at 0°C, with a discharge capacity of C2, left at 10 min, and a capacity retention rate η1=C2 / C1*100%, and the test results are recorded in Table 3.
[0166] (4) Battery cycle life test:
[0167] The batteries prepared in the above embodiments and comparative examples were charged at 5C rate and discharged at 1C rate for 500 cycles at room temperature. Specifically: the battery was charged to 4.45V at 5C at 25°C, with a cut-off current of 0.2C, and then discharged to 3V at 1C, with the discharge capacity recorded as A1. The charge and discharge steps were repeated 500 times, and the discharge capacity of the 500th cycle was recorded as A2. After 500 5C / 1C cycles, the retention rate η2=A2 / A1*100%, and the test results are recorded in Table 3.
[0168] (5) Battery lithium deposition and powder loss test:
[0169] The batteries prepared in the above embodiments and comparative examples are fully charged at 6C, discharged at 0.5C, and the cells are dissected after 20 cycles of charge and discharge to check the lithium deposition and powder loss. Specifically: the battery is charged to 4.45V at 5C at 25°C, with a cut-off current of 0.2C, and then discharged to 3V at 0.5C, and repeated 20 times. The battery is disassembled under the condition of 100% SOC of the battery, and a complete negative electrode sheet and separator are obtained after disassembly. It is observed whether lithium deposition occurs on the surface of the negative electrode sheet (according to the degree of lithium deposition, it is divided into: no lithium deposition, slight lithium deposition, lithium deposition and severe lithium deposition), and whether the negative electrode coating falls off or powder falls off (according to the degree, it is divided into: no powder loss, powder loss and coating loss), and the test results are recorded in Table 3.
[0170] (6) Peel strength test of negative electrode
[0171] The peel strength of the negative electrode sheets prepared in the above embodiments and comparative examples is the peel strength between the base coating and the negative electrode collector, and is tested by using a tensile machine in a 180° peeling mode after the negative electrode sheets are cold pressed; specifically: take the negative electrode sheet after rolling, cut it into a size of 24 mm wide and 20 cm long, adhere one side of the electrode sheet to the glass plate with double-sided tape, use a tensile machine to stretch the foil upward at 180° to separate the negative electrode collector foil from the base coating, read the average tensile force value N of the tensile machine, and the peel strength value is N divided by the width 0.024 m, that is, the peel strength of the negative electrode sheet is obtained, the unit is N / m, and the test results are recorded in Table 3.
[0172] Table 2
[0173]
[0174] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet includes a negative electrode collector, a primer layer and a negative electrode active material layer located on one side or both sides of the negative electrode collector, the primer layer is located between the negative electrode collector and the negative electrode active material layer, the primer layer includes a three-dimensional structure formed by a first conductive adhesive, the first conductive adhesive includes a first carbon nanotube, and the negative electrode sheet satisfies the following relationship: 1.2≤B / K≤3.4, wherein B is the aspect ratio of the first carbon nanotube, and K is the tensile strength of the negative electrode collector, in MPa.
2. The negative electrode sheet according to claim 1, wherein: The first conductive adhesive comprises a first adhesive layer located on at least a portion of the surface of the first carbon nanotube; And / or, the tensile strength K of the negative electrode current collector is 300Mpa-1000Mpa; and / or, the aspect ratio B of the first carbon nanotube is ≥1000; And / or, the primer layer further includes a first carbon black, and the first carbon black is located in the gap of the three-dimensional structure; and / or, the first carbon nanotubes include first multi-walled carbon nanotubes and / or first single-walled carbon nanotubes; and / or, the surface of the first carbon nanotube comprises one or more of the following functional groups: carboxyl, hydroxyl, amine, silane; And / or, the first carbon nanotube is a carbon nanotube modified by a first modifier, and the first modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate, methacrylic acid, and maleic acid.
3. The negative electrode sheet according to claim 2, wherein: The base coating also includes a first dispersant; and / or, the ratio of the weight of the first multi-walled carbon nanotube to the weight of the first single-walled carbon nanotube is (2-5):1; And / or, the ratio of the weight of the first carbon nanotube to the weight of the first carbon black is (1.22-5.84):1; And / or, the ratio of the thickness of the negative electrode current collector to the thickness of the primer layer is (6-10):1; And / or, the thickness of the negative electrode current collector is 3 μm-15 μm; and / or, the thickness of the primer layer is 0.3 μm-0.6 μm; And / or, the average particle size of the first carbon black is 10nm-300nm, preferably 500nm-3000nm.
4. The negative electrode sheet according to claim 3, wherein: The first bonding layer further comprises one or more polymers selected from styrene-butadiene rubber, nitrile-butadiene rubber, polyacrylic acid and polyimide; And / or, the glass transition temperature of the first adhesive layer is -10°C to 80°C; and / or, the average thickness of the first bonding layer on the first carbon nanotube is 20 nm-200 nm; and / or, the molecular weight of the polymer in the first bonding layer is ≥ 1,000,000 g / mol; And / or, the weight ratio of the first carbon nanotubes to the first bonding layer in the first conductive adhesive is (34%-68%):(66%-32%); and / or, the first dispersant comprises one or more of polyvinyl pyrrolidone, carboxymethyl cellulose and polyacrylic acid; and / or, the molecular weight of the first dispersant is 10000 g / mol-100000 g / mol; And / or, based on the total weight of the primer layer, the weight content of the first conductive binder is 72%-86%, the weight content of the first carbon black is 10%-20%, and the weight content of the first dispersant is 4%-8%.
5. The negative electrode sheet according to claim 1, wherein: The average diameter of the first carbon nanotubes is 6nm-10nm; And / or, the average tube length of the first carbon nanotubes is 13 μm-20 μm; And / or, the wall thickness of the first carbon nanotube is 6nm-9nm; and / or, the weight proportion of the first carbon nanotubes having an average tube length of ≥8 μm in all the first carbon nanotubes is ≥50%; And / or, the surface density of the primer layer is 0.2 g / m 2 -0.8g / m 2 .
6. The negative electrode sheet according to any one of claims 1 to 5, wherein: The negative electrode active material layer includes a three-dimensional network skeleton and a negative electrode active material located in the three-dimensional network skeleton, wherein the three-dimensional network skeleton is formed by a second conductive binder, and the second conductive binder includes a second carbon nanotube and a second bonding layer located on at least a portion of the surface of the second carbon nanotube; And / or, the peel strength between the primer layer and the negative electrode current collector is ≥10 N / m.
7. The negative electrode sheet according to claim 6, wherein: The negative electrode sheet satisfies the following relationship: 14.4≤K1 / K2≤43, wherein K1 is the crosslinking coefficient between the first conductive binder and the first carbon black, and K2 is the crosslinking coefficient between the second conductive binder and the negative electrode active material; and / or, K1 is 3.6-8.6, preferably 4-5; and / or, K2 is 0.2-2.5, preferably 1-2; and / or, the surface of the second carbon nanotube comprises one or more of the following functional groups: carboxyl, hydroxyl, amine, silane; And / or, the second carbon nanotubes are carbon nanotubes modified by a second modifier, and the second modifier includes one or more of diethyl adipate, diethyl dimethylmalonate, diethyl suberate, dimethyl malonate, dimethyl suberate, methyl valerate, propyl butyrate, n-dodecyltrimethoxysilane, silane coupling agent, trimethylsilane, hexadecyltrimethylammonium tetrafluoroborate, N-(coconut alkyl)-N,N,N-trimethyl methylammonium sulfate, cocamidopropyl betaine, hexadecyltrimethylammonium acetate and hexadecyltrimethylammonium nitrate, methacrylic acid, and maleic acid.
8. The negative electrode sheet according to claim 6, wherein: The aspect ratio of the second carbon nanotube is ≥1000; And / or, the average diameter of the second carbon nanotubes is 6nm-10nm; And / or, the average tube length of the second carbon nanotubes is 13 μm-20 μm; And / or, the wall thickness of the second carbon nanotube is 6nm-7nm; and / or, the weight proportion of the second carbon nanotubes having an average tube length of ≥8 μm in all the second carbon nanotubes is ≥50%; And / or, the surface density of the negative electrode sheet is 26.82 g / m 2 -134.1g / m 2 .
9. The negative electrode sheet according to claim 7 or 8, wherein: The negative electrode active material layer further includes a negative electrode binder and a thickener, wherein the thickener includes one or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, and polyacrylic acid, and the negative electrode binder includes one or more of styrene-butadiene rubber, styrene-acrylic emulsion, nitrile rubber, polyimide, and acrylic; Preferably, the molecular weight of the thickener is 500000 g / mol-1000000 g / mol; Preferably, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 90%-99%, the weight content of the second conductive binder is 0.25%-5%, the negative electrode binder includes 1%-2%, and the weight content of the thickener is ≤1%; And / or, the surface density of the negative electrode active material layer is 26.62 g / m 2 -126.1g / m 2 .
10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 9.
Citation Information
Cited By
Positive pole piece, secondary battery and electronic device
CN121011623A
Composite negative electrode, preparation method thereof and lithium ion battery
CN121726332A
Composite negative electrode, method for preparing the same, and lithium ion battery
CN121726332B
Negative electrode, preparation method thereof and electric device
CN121905792A